IDENTIFIKASI BAKTERI ESCHERICHIA COLI O157:H7 PADA FESES PENDERITA DIARE DENGAN METODE KULTUR DAN PCR - Rizky, Vincentia Ade; Siregar, Sa’adah; Krisdianilo, Visensius; Rahayu, Asvia; Syafrina Ginting, Suventi; ., Kartini (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Escherichia coli O157: H7 is the main cause of foodborne disease in several countries, one of which is diarrhea. Diarrheal disease is still a major problem in Indonesia that needs treatment and study from various aspects. The conventional method of laboratory examination such as culture is a method that is often carried out, but in making the diagnosis requires a long time, the number of samples is large, and the results are less accurate because contamination can occur. Another more accurate technique for detecting Escherichia coli O157: H7 is the PCR technique. This study aims to identify the Escherichia coli O157: H7 bacteria by culture method and PCR. The results showed that the culture method and PCR of 8 isolated samples 4 showed positive results for the bacterium Escherichia coli O157: H7. However, the PCR method is more selective and faster than the culture method.